Optimizing athletic engagement and performance of obese students: an adaptive approach through basketball in physical education - Slimi, Oumayma; Muscella, Antonella; Marsigliante, Santo; Bahloul, Mourad; Badicu, Georgian; Alghannam, Abdullah F.; Yagin, Fatma Hilal (Frontiers in Sports and Active Living, 2025)
IntroductionObesity in adolescents is associated with reduced physical activity and athletic engagement, highlighting the need for tailored physical education programs. This study evaluated the effects of a 7-week adapted basketball program on the performance and athletic engagement of students with obesity.MethodsSixty-two students with obesity (23 boys, 39 girls, aged 15-17) were randomly assigned to an experimental group (EG, n = 30; 11 boys, 19 girls) participating in adapted basketball sessions or a control group (CG, n = 32; 12 boys, 20 girls) attending standard basketball lessons. Both groups completed 52-minute sessions twice weekly. Pre- and post-intervention assessments included a questionnaire evaluating perceptions of physical education and athletic performance during final matches.ResultsThe EG showed significant improvements in interest, motivation (p < 0.05), perceived competence (p < 0.001), and reduced exercise difficulty (p < 0.001). Perceived fitness levels increased significantly only in EG girls (p = 0.013). In contrast, no significant changes were observed in the CG before and after the intervention for any of the parameters. During matches, the EG outperformed the CG, with more successful shots (girls: p = 0.0004; boys: p = 0.012), fewer missed shots (girls: p = 0.033; boys: p = 0.046), and more successful passes (p = 0.032, η² = 0.042).DiscussionThese results demonstrate that adapted physical education programs can serve as effective interventions for improving physical activity and promoting inclusion among adolescents with obesity while also serving as a preventive measure against obesity.